Managing the Career Plateau - Ference, Thomas P.; Stoner, James A. F.; Warren, E. Kirby (Academy of Management Review, 1977)
Managerial careers are characterized by early rapid upward mobility followed by inevitable leveling-off or plateauing. Based on interviews with managers in nine major organizations, a general dynamic model of managerial careers is presented. Some key issues associated with the career plateau are isolated and suggestions for managing the plateau process are offered.